A Generic Framework for Fourier-Domain Optical Coherence Tomography Imaging: Software Architecture and Hardware Implementations - Yin-Peng Huang; Ting-Yen Tsai; Ting-Hao Chen; Chuan-Bor Chueh; You-Nan Tsai; Yu-Wei Chang; Yi-Chung Wu; Hung-Wen Chen; Meng-Tsan Tsai; Yi-Ping Hung; Hsiang-Chieh Lee (IEEE Access, 2020)
Fourier-domain optical coherence tomography (FD-OCT), including spectral-domain OCT (SD-OCT) and swept-source OCT (SS-OCT), allows the volumetric imaging of the tissue architecture with a faster speed and higher detection sensitivity than does time-domain OCT. Although the hardware implementations of SD-OCT and SS-OCT are different, these technologies share very similar signal processing steps for image reconstruction. In this study, we developed hardware implementations and software architectures to design a generic framework for FD-OCT. For SD-OCT systems, an external synchronization approach was used to realize a data acquisition schematic similar to that used in SS-OCT by carefully managing the timing clocks in the detection unit and for the waveform generation. In addition, by utilizing modules and factory concepts, a software engine can be developed that supports various acquisition devices and software operations or image processing functions with high operation flexibility while maintaining its robustness. Data processing and data saving were optimized using the parallel computing method with the OpenMP library and by leveraging the parallelism within the acquired data, respectively.